Psychosomatic disorders in clinical practice - I. R. Mukharovskaya; M. V. Markov; Ts. B. Abdryakhimova; K. I. Kleban; D. M. Sapon (Kazimierz Wielki University, 2019)
Psychosomatic disorders in a broad sense represent a group of conditions that are different in etiology and pathogenesis, characterizing the interconnection and mutual influence of the somatic and mental sphere: psychosomatic diseases, somatoform disorders, somatogenia, psychogenia, personality traits and behavior that lead to the development of somatic diseases. Diagnosis of psychosomatic disorders in patients in the somatic network is of great practical importance in connection with the early detection of pathology and effective action on the immediate causes of its occurrence.